Molecular detection of dugbe orthonairovirus in cattle and their infesting ticks (Amblyomma and Rhipicephalus (Boophilus)) in Nigeria. - Oluwafemi Babatunde Daodu; Albert Eisenbarth; Ansgar Schulz; Julia Hartlaub; James Olukayode Olopade; Daniel Oladimeji Oluwayelu; Martin H Groschup (Public Library of Science (PLoS), 2021)
Dugbe orthonairovirus (DUGV), a tick-borne zoonotic arbovirus, was first isolated in 1964 in Nigeria. For over four decades, no active surveillance was conducted to monitor the spread and genetic variation of DUGV. This study detected and genetically characterized DUGV circulating in cattle and their infesting ticks (Amblyomma and Rhipicephalus (Boophilus)) in Kwara State, North-Central Nigeria. Blood and or ticks were collected from 1051 cattle at 31 sampling sites (abattoirs and farms) across 10 local government areas of the State. DUGV detection was carried out by RT-qPCR, and positive samples sequenced and phylogenetically analysed. A total of 11824 ticks, mostly A. variegatum (36.0%) and R. (B.) microplus (63.9%), were obtained with mean tick burden of 12 ticks/cattle. Thirty-four (32 A. variegatum and two R. (B.) microplus) of 4644 examined ticks were DUGV-positive, whereas all of the cattle sera tested negative for DUGV genome. Whole genome sequence (S, M and L segments) and phylogenetic analyses indicate that the positive samples shared up to 99.88% nucleotide identity with and clustered around the Nigerian DUGV prototype strain IbAr 1792. Hence, DUGV with high similarity to the previously characterised strain has been detected in Nigeria. To our knowledge, this is the first report of DUGV in North-Central Nigeria and the most recent information after its last surveillance in 1974.